2009
DOI: 10.1038/sj.bjc.6605318
|View full text |Cite
|
Sign up to set email alerts
|

CD8+ lymphocytes/ tumour-budding index: an independent prognostic factor representing a ‘pro-/anti-tumour’ approach to tumour host interaction in colorectal cancer

Abstract: Background:The tumour-host interaction at the invasive front of colorectal cancer, including the epithelial–mesenchymal transition and its hallmark ‘tumour budding', is an important area of investigation in terms of prognosis. The aim of this study was to determine the prognostic impact of a ‘pro-/anti-tumour' approach defined by an established ‘pro-tumour' (tumour budding) and host-related ‘anti-tumour' factor of the adaptive immunological microenvironment (CD8+ lymphocytes).Methods:Double immunostaining for … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
126
0
1

Year Published

2011
2011
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 117 publications
(136 citation statements)
references
References 35 publications
9
126
0
1
Order By: Relevance
“…There is a strong association between budding and the presence of lymph node metastases and lymphovascular invasion, 11,12,[15][16][17][18][19][20][21][22][23][24][25][26][27][28][29][30][31][32] defined by the presence of tumor cells within an endothelium-lined space, and it has been suggested that buds represent the part of the tumor that has gained the ability to invade lymphatics and vascular channels. This idea is supported by two intriguing morphological studies: Morodomi et al 33 examined serial sections of high-budding areas to demonstrate that budding nests are often found adjacent to areas of lymphovascular space invasion, and, in a more recent study, Ohtsuki et al 31 performed double staining for anti-cytokeratin antibodies and anti-lymphatic antibodies, finding that a number of 'buds' at the invasive edge of a tumor are in fact located in small lymphatic spaces.…”
Section: Morphological Featuresmentioning
confidence: 99%
See 4 more Smart Citations
“…There is a strong association between budding and the presence of lymph node metastases and lymphovascular invasion, 11,12,[15][16][17][18][19][20][21][22][23][24][25][26][27][28][29][30][31][32] defined by the presence of tumor cells within an endothelium-lined space, and it has been suggested that buds represent the part of the tumor that has gained the ability to invade lymphatics and vascular channels. This idea is supported by two intriguing morphological studies: Morodomi et al 33 examined serial sections of high-budding areas to demonstrate that budding nests are often found adjacent to areas of lymphovascular space invasion, and, in a more recent study, Ohtsuki et al 31 performed double staining for anti-cytokeratin antibodies and anti-lymphatic antibodies, finding that a number of 'buds' at the invasive edge of a tumor are in fact located in small lymphatic spaces.…”
Section: Morphological Featuresmentioning
confidence: 99%
“…Lugli et al 23 have demonstrated that a peritumoral lymphocytic reaction is associated with improved prognosis in the setting of tumor budding, suggesting that the immune response might target the tumor buds. The nature of the stroma at the invasive margin may provide further prognostic information, with myxoid stroma being associated with worse prognosis, 20,39 but further studies are needed to confirm the reproducibility and prognostic importance of these findings.…”
Section: Morphological Featuresmentioning
confidence: 99%
See 3 more Smart Citations